Digital Leadership Capability in Muhammadiyah Charity Units A Literature Review - Abdullah, Abdullah; Suhariadi, Fendy; Miftahusurur, M. (RSF Conference Series: Business, Management and Social Sciences, 2024)
This research explores digital leadership capabilities in Muhammadiyah business charity units through a literature review. In the midst of rapid digital transformation, the ability to adopt and implement digital technology has become crucial for nonprofit organizations, including Muhammadiyah. Using a systematic literature review methodology, this study identifies and analyzes previous studies on digital leadership in the context of nonprofit and religious organizations. The results of this review demonstrate that digital leadership capabilities in Muhammadiyah charity units are influenced by factors such as technological skills, strategic vision, organizational support, and culture of innovation. This research also found that although several studies have discussed digital leadership, a significant gap remains in the literature regarding specific implementations in the context of Muhammadiyah. Based on these findings, this article provides practical recommendations for developing digital leadership capabilities that improve the effectiveness and operational efficiency of Muhammadiyah charity units. In addition, this study suggests directions for further research that focus on implementation strategies and impact evaluation of digital leadership in the nonprofit sector.